Comparison of pre and post Global longitudinal Strain imaging in thrombolytic and primary percutaneous coronary intervention in acute ST elevation Anterior Myocardial infarction (University Heart Journal, 2020)
Abstract not availableUniversity Heart Journal Vol. 16, No. 1, Jan 2020; 11-15